2018
DOI: 10.1093/jee/toy012
|View full text |Cite
|
Sign up to set email alerts
|

Age-Stage, Two-Sex Life Tables of the Lady Beetle (Coleoptera: Coccinellidae) Feeding on Different Aphid Species

Abstract: Life table and predation data were collected for Coccinella septempunctata (Linnaeus) (Coleoptera: Coccinellidae) feeding on three different host aphid species, Aphis craccivora (Koch) (Hemiptera: Aphididae), Lipaphis erysimi (Kaltenbach) (Hemiptera: Aphididae), and Myzus persicae (Sulzer) (Hemiptera: Aphididae), under laboratory conditions, using age-stage, two-sex life table. The preadult developmental period of C. septempunctata was the shortest on M. persicae (21.12 d) and the longest on A. craccivora (28.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
22
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 47 publications
7
22
9
Order By: Relevance
“…The results of present study revealed that statistically maximum male and female longevity was recorded on D. noxia while minimum longevity was recorded on L. erysimi . These results contrary with the study conducted on C. septempunctata that the adult longevity was maximum on L. erysimi than other aphid species (24, 38). In current study, highest fecundity was recorded on D. noxia .…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The results of present study revealed that statistically maximum male and female longevity was recorded on D. noxia while minimum longevity was recorded on L. erysimi . These results contrary with the study conducted on C. septempunctata that the adult longevity was maximum on L. erysimi than other aphid species (24, 38). In current study, highest fecundity was recorded on D. noxia .…”
Section: Discussioncontrasting
confidence: 99%
“…In current study, highest fecundity was recorded on D. noxia . These results contrary with the study carried out on C. septempunctata where the maximum fecundity was reported on M. persicae (24, 39). There is a relation among predator longevity and fecundity.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations